Integrating reflective activities in eportfolios to support the development of abilities in self-managed experiential learning. Issue 5 (3rd September 2017) - Cowan, John; Peacock, Susi
Abstract: This article presents the case for self-managing and self-regulating learners to link their various forms of reflection explicitly, and to do so within an ePortfolio, in order to support the development of higher-level abilities such as problem-solving, critiquing, decision-making, empathising and resolving conflicts. It explores the reflective options for self-managed experiential learning, and concentrates upon what three forms of reflection ( reflection - for, -on - and in - action ) entail, and could contribute to learning and development. It also addresses how linking previous reflections ( composted reflections ) can contribute to the development of higher-level abilities. An ePortfolio is taken as a natural and effective location for this integration. Guidance is offered, requiring modest tutorial activity to generate and maintain learner involvement in the development of linked reflections in a learner's assorted records and reflections housed in an ePortfolio. Suggestions for gathering learner constructive feedback on such initiatives are included.